A single immunization with cellular vaccine confers dual protection against SARS‐CoV‐2 and cancer. Issue 8 (7th June 2022) - Shimizu, Kanako; Ueda, Shogo; Kawamura, Masami; Satoh, Mikiko; Fujii, Shin‐ichiro
Abstract: The efficacy of current coronavirus disease 2019 (COVID‐19) vaccines has been demonstrated; however, emerging evidence suggests insufficient protection in certain immunocompromised cancer patients. We previously developed a cell‐based anti‐cancer vaccine platform involving artificial adjuvant vector cells (aAVCs) capable of inducing a strong adaptive response by enhancing the innate immunity. aAVCs are target antigen‐transfected allogenic cells that simultaneously express the natural killer T‐cell ligand–CD1d complex on their surface. In the present study, we applied this system for targeting the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike protein (CoV‐2‐S) using CoV‐2‐S‐expressing aAVCs (aAVC‐CoV‐2) and evaluated the immune response in a murine model. A single dose of aAVC‐CoV‐2 induced a large amount of CoV‐2‐S‐specific, multifunctional CTLs in addition to CD4 + T‐cell‐dependent anti‐CoV‐2‐S‐specific Abs. CoV‐2‐S‐specific CTLs infiltrated the lung parenchyma and persisted as long‐term memory T cells. Furthermore, we immunized mice with CoV‐2‐S‐ and tumor‐associated antigen (TAA)‐co‐expressing aAVCs (aAVC‐TAA/CoV‐2) and evaluated whether the anti‐SARS‐CoV‐2 and antitumor CTLs were elicited. We found that the aAVC‐TAA/CoV‐2‐S therapy exerted apparent antitumor effects and induced CoV‐2‐S‐specific CTLs. These findings suggest aAVC‐TAA/CoV‐2‐S therapy as a promising vaccine candidate for preventing COVID‐19, as well as enhancing the effectiveness of cancer therapies. Abstract : Due to the insufficient efficacy of current COVID‐19 vaccines in cancer patients, such high‐risk groups require more efficient vaccines that induce a strong memory response and provide dual protection against cancer and COVID‐19. We showed that SARS‐CoV‐2 spike protein‐expressing artificial adjuvant vector cells (aAVC‐CoV‐2) elicited the production of robust and long‐lived spike protein‐specific multifunctional cytotoxic T lymphocytes (CTLs) capable of infiltrating the lung parenchyma, thus illustrating the distinct advantage of using aAVC‐CoV‐2 as a second‐line vaccine, especially for individuals who are resistant to the current COVID‐19 vaccines. In addition, aAVCs expressing tumor‐associated antigen (TAA) and spike protein caused a dual induction of TAA‐specific CD8+ T cells and spike protein‐specific CD8+ T cells and provided sufficient protection against tumors, suggesting an effective strategy for treating cancer patients while simultaneously preventing SARS‐CoV‐2 infection.